Predictors of Adolescent Academic Achievement: The Role of Individual and Family Socioeconomic Factors - Melly Latifah; Rizky Amelia (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Academic achievement is affected by external and internal factors. This study generally aims to examine the influence of family characteristics (per capita income and parental education), individual characteristics (age and gender), cognitive intelligence, and self-regulated learning toward academic achievement in adolescents. A total of 91 samples (Mage=13.9 years) with the largest percentage of the respondents were women were selected from two different junior high schools in Bogor area. Cognitive intelligence, self-regulated learning, and academic achievement were measured using Riley Inventory Basic of Learning Skills (RIBLS), Motivated Strategies for Learning Questionnaire (MSQL), and student academic record, respectively. The partial regression analysis showed there was a negative effect of mother’s education on self-regulated learning. Gender was found to positively predicted cognitive intelligence. The regression analysis also showed that parental education and cognitive intelligence positively predicted adolescent academic achievement. Per capita income, gender, and self-regulated learning showed no significant effects on academic achievement.